Utilization of palliative care in patients hospitalized with heart failure: A contemporary national perspective - Alqahtani, Fahad (Clin Cardiol, 2018)
BACKGROUND: Despite advances in therapy, heart failure (HF) patients have significant symptom burden and poor quality of life. However, data on palliative care (PC) utilization in this population are scarce. We sought to assess national trends in PC utilization in patients admitted with acute HF. METHODS: Adults hospitalized with HF without acute coronary syndrome were identified in the National inpatient sample. PC was identified using ICD‐9‐CM‐Code V66.7. Trends in PC utilization, its predictors and its association with length‐of‐stay and cost were assessed. RESULTS: A total of 939 680 HF patients were hospitalized with HF between 2003 and 2014. Of those,1.2% received PC during the hospitalization, with an upward trend in the use of PC over time (0.12% in 2003 to 3.6% in 2014, P < 0.001). Compared with patients who did not receive PC, those who had PC were older (79 ± 12 vs 69 ± 16 years), and had higher prevalence of Caucasian race (73.4% vs 51.8%), coronary disease (45.6% vs 39.3%), chronic renal disease (79.3% vs 42.8%), and pulmonary hypertension (28.3% vs 15.1%) (P < 0.001). In‐hospital mortality (35.2% vs 2.2%), length‐of‐stay (9 ± 13 days vs 6 ± 6, P < 0.001), cost ($19 984 ± 42 922 vs $11 921 ± 18 175), and non‐home discharges (46% vs 19.2%) (P < 0.001) were higher in the PC group. In‐hospital mortality in PC group trended downward over time (69% in 2003 vs 29% in 2014, P < 0.001). CONCLUSION: PC is being utilized in an increasing but overall small number of patients hospitalized with HF. Further research is needed to identify the optimal role and timing of PC in HF patients.